A new method of closing the defects of chest wall - G. Z. Dambaev; V. E. Gunter; S. G. Philippov; E. G. Sokolovich; E. B. Topolnitsky; A. V. Doroshenko (Бюллетень сибирской медицины)
There was worked out a new method of plastics of chest wall defects by means of construction from nikelide of titan. An experimental examination of effectiveness of the method with the use of clinical, roentgenological and morphologic control was carried out. The method provides normalization of biomechanics of respiration by means of restoration of osteochondrous skeleton and liquidation of cosmetic defection.